Dance studies the basics - Butterworth, Jo. (London New York Routledge, 2012)
"Dance Studies: The Basics is a concise introduction to the study of dance ranging from the practical aspects such as technique and to more theoretical considerations such as aesthetic appreciation and the place of dance in different cultures. Including examples from dance forms such as ballet, jazz, tap, contemporary and urban, this book answers questions such as: Exactly how do we define 'dance'? What kinds of people dance and what kind of training is necessary? How are dances made? What do we know about dance history? Featuring a glossary, chronology of dance history and list of useful websites, this book is the ideal starting point for anyone interested in the study of dance"-- Provided by publisher.
Jocelyn C. Pinzon (Recommending Faculty) : Arts and Humanities Cluster
Includes bibliographical references and index.
Keywords: Dance; Choreography; Dance -- History